2017
DOI: 10.1111/mmi.13770
|View full text |Cite
|
Sign up to set email alerts
|

Viscous drag on the flagellum activates Bacillus subtilis entry into the K‐state

Abstract: Bacillus subtilis flagella are not only required for locomotion but also act as sensors that monitor environmental changes. Although how the signal transmission takes place is poorly understood, it has been shown that flagella play an important role in surface sensing by transmitting a mechanical signal to control the DegS-DegU two-component system. Here we report a role for flagella in the regulation of the K-state, which enables transformability and antibiotic tolerance (persistence). Mutations impairing fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
(111 reference statements)
5
10
1
Order By: Relevance
“…By additionally investigating a strain harboring a degU-yfp fusion, Diethmaier et al also suggested an increased level of DegU~P to be present in the hag-mutant (Diethmaier et al, 2017), which is consistent with our conclusions. In addition, the authors detected a reduced expression of comK in a strain with the degU32 variant, which produces a form of DegU~P with higher stability (Diethmaier et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…By additionally investigating a strain harboring a degU-yfp fusion, Diethmaier et al also suggested an increased level of DegU~P to be present in the hag-mutant (Diethmaier et al, 2017), which is consistent with our conclusions. In addition, the authors detected a reduced expression of comK in a strain with the degU32 variant, which produces a form of DegU~P with higher stability (Diethmaier et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…At this point however, we cannot provide a reasonable explanation for the increased transformation frequency of Δhag degU32. Diethmaier et al proposed that increased DegU~P and lower comK expression in the flagellar mutants and in a strain with straight flagella was caused by a lower viscous load (Diethmaier et al, 2017). In line with this report, we also observed that higher viscosity in the medium resulted in an increased transformation frequency.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations